Nitrogen metabolic rate and differential ammonia volatilization regulate resistance against opportunistic fungus Alternaria alternata in tobacco - Zhixiao Yang; Yi Chen; Yi Wang; Haiqian Xia; Shaoqing Zheng; Shengdong Xie; Yi Cao; Jiemin Liu; Shafaque Sehar; Yingchao Lin; Yushuang Guo; Imran Haider Shamsi (Frontiers in Plant Science, 2022)
Nutritional correlations between plants and pathogens can crucially affect disease severity. As an essential macronutrient, the availability of nitrogen (N) and the types of N content play a fundamental part not only in energy metabolism and protein synthesis but also in pathogenesis. However, a direct connection has not yet been established between differences in the level of resistance and N metabolism. Pertinently, former studies hold ammonia (NH3) accountable for the development of diseases in tobacco (Nicotiana tabacum L.) and in some post-harvest fruits. With a purpose of pinpointing the function of NH3 volatilization on Alternaria alternata (Fries) Keissl pathogenesis and its correlation with both N metabolism and resistance differences to Alternaria alternata infection in tobacco, leaf tissue of two tobacco cultivars with susceptibility (Changbohuang; CBH), or resistance (Jingyehuang; JYH) were analyzed apropos of ammonia compensation point, apoplastic NH4+ concentration, pH value as well as activities of key enzymes and N status. At the leaf age of 40 to 60 d, the susceptible cultivar had a significantly higher foliar apoplastic ammonium (NH4+) concentration, pH value and NH3 volatilization potential compared to the resistant one accompanied by a significant reduction in glutamine synthetase (GS), which in particular was a primary factor causing the NH3 volatilization. The NH4+ concentration in CBH was 1.44 times higher than that in JYH, and CBH had NH3 compensation points that were 7.09, 6.15 and 4.35-fold higher than those of JYH at 40, 50 and 60 d, respectively. Moreover, the glutamate dehydrogenase (GDH) activity had an upward tendency related to an increased NH4+ accumulation in both leaf tissues and apoplast but not with the NH3 compensation point. Collectively, our results strongly suggest that the accumulation of NH3 volatilization, rather than NH4+ and total N, was the primary factor inducing the Alternaria alternata infection in tobacco. Meanwhile, the susceptible cultivar was characterized by a higher N re-transfer ability of NH3 volatilization, in contrast to the disease–resistant cultivar, and had a stronger capability of N assimilation and reutilization. This study provides a deeper understanding of the pathogenicity mechanism induced by Alternaria alternata, which is useful for breeding Alternaria alternata-resistant varieties of tobacco, at the same time, our research is also conducive to control tobacco brown spot caused by Alternaria alternata in the field.